حق الدفا ع الشرعي دراسة مقارنة بني الشريعة الإسلامية و القانون الدوي - عبد الحكيم بوصوارة (My University, 2025)
Abstract Islam has established peace as a fundamental principle, with war being an exceptional circumstance, intended solely to repel injustice and aggression. Islam has sanctioned the right to legitimate self-defense and considered it a human duty to protect oneself or others, and one's country and homeland from any unlawful, immediate aggression, using the necessary force to repel such aggression. It has forbidden aggressive warfare, deeming it a crime. Allah Almighty says: {And fight in the way of Allah those who fight you, but do not transgress. Indeed. Allah does not like transgressors} (Al-Baqarah 2:190). Islam also defined collective legitimate defense, clarified its limits, concept, and content, and laid down its rules and provisions in detail more than fourteen centuries ago. The Book of Allah descended with truth, and the Sunnah of our Prophet Muhammad (peace be upon him) came with all the principles and treaties that dispel doubt and legislate for and preserve all rights, foremost among them the right to legitimate defense in Islam, with the aim of preserving and defending Islamic lands. Similarly, positive laws, especially international law, have affirmed numerous agreements, treaties, and regulatory texts that govern international relations within the international community. These have included various foundations, controls, and principles that stipulate the legitimacy of the right to legitimate defense in cases of aggression. They have clarified its forms and conditions for its exercise within organized legal frameworks, thus guaranteeing all rights and ensuring all obligations in order to enjoy this right. Therefore, our study of this topic is a comparison between the Islamic and international systems, with the aim of clarifying all aspects related to the exercise of this right within the framework of the principles of Islamic Sharia and the rules of international law. ................................. ملخص الدراسة : لقد أقر الإسلام السلام كقاعدة أساسية، وما الحرب إلا حالة إستثنائية، يقصد من ورائها دفع الظلم والعدوان، إذ شرع الحق في الدفاع الشرعي عن النفس وإعتبره واجب الإنسان في حماية نفسه أو غيره، وحقه في بلده ووطنه من كل إعتداء حال غير مشروع، بالقوة اللازمة لدفع هذا الإعتداء، وحرم الحرب العدوانية وجعلها جريمة، قال الله تعالى : { وقاتلوا في سبيل الله الذين يقاتلونكم ولا تعتدوا إن الله لا يحب المعتدين }، كما عرف الإسلام الدفاع الشرعي الجماعي وبين حدوده ومفهومه ومضمونه، ووضع قواعده وأحكامه بالتفصيل منذ أكثر من أربعة عشر قرنا من الزمن، فنزل كتاب الله بالحق، وجاءت سنة نبينا محمد صلى الله عليه و سلم بكافة المبادئ و المعاهدات التي تقطع الشك باليقين، و تشرع لجميع الحقوق و تحفظها وعلى رأسها حق الدفاع الشرعي في الإسلام، وهذا بغاية حفظ البلاد الإسلامية والدفاع عنها . كما أقرت القوانين الوضعية وخاصة القانون الدولي، العديد من الإتفاقيات والمعاهدات و النصوص التنظيمية، التي تنظم العلاقات الدولية في المجتمع الدولي، فجاءت متضمنة لمختلف الأسس والضوابط والمبادئ التي تنص على شرعية حق الدفاع الشرعي في حالة العدوان، فبينت صوره وشروط ممارسته في أطر قانونية منظمة، فكفلت جميع الحقوق وضمنت كافة الإلتزامات في سبيل التمتع بهذا الحق، فجاءت دراستنا لهذا الموضوع كمقارنة بين النظامين الإسلامي و الدولي، بهدف توضيح كافة الجوانب المتعلقة بممارسة هذا الحق في إطار ما تحتويه مبادئ الشريعة الإسلامية وقواعد القانون الدولي. .............................. Résumé: L’islam a établi la paix comme principe fondamental, la guerre n’étant qu’une situation exceptionnelle visant à repousser l’injustice et l’agression. Le droit à la légitime défense a été légiféré comme un devoir de l’homme pour protéger sa personne ou autrui, ainsi que son pays et sa patrie contre toute agression illégitime, en utilisant la force nécessaire pour repousser cette attaque. L’islam interdit la guerre offensive et la considère comme un crime. Dieu Tout-Puissant a dit : « Combattez dans le sentier de Dieu ceux qui vous combattent, mais ne transgressez pas. Certes, Dieu n’aime pas les transgresseurs ». L’islam a également défini la défense légitime collective, en précisant ses limites, son concept et sa portée. Il en a établi les règles et les dispositions détaillées depuis plus de quatorze siècles, à travers le Livre de Dieu révélé avec vérité et la Sunna de notre Prophète Mohammed (paix et salut sur lui), laquelle renferme tous les principes et traités qui dissipent tout doute, consacrent tous les droits, et notamment celui de la légitime défense en islam, dans le but de préserver et de défendre les pays musulmans. Par ailleurs, les lois positives, et en particulier le droit international, ont adopté de nombreuses conventions, traités et textes réglementaires régissant les relations internationales. Ces instruments énoncent les fondements, conditions et principes encadrant la légitimité du droit à la légitime défense en cas d’agression. Ils définissent ses formes et les modalités de son exercice dans un cadre juridique organisé, garantissant tous les droits et engagements nécessaires à l’exercice de ce droit. Notre étude aborde ce sujet en tant que comparaison entre le système islamique et le système international, afin d’éclairer tous les aspects liés à l’exercice de ce droit, à la lumière des principes de la charia islamique et des règles du droit international.
Keywords: Keywords: Peace; War; Legitimate Defense; Islam; International Law .; الكلمات المفتاحية: السلام، الحرب، الدفاع الشرعي، الإسلام، القانون الدولي .; Mots-clés : paix; guerre; légitime défense; islam; droit international.